UPAYA PENINGKATAN KESADARAN KESEHATAN REPRODUKSI REMAJA : MENSTRUASI PADA SISWA SDN 1 PAPAHAN - Betty Kusdhiarningsih; Nurul Gilang Abriani; Exda Hanung Lidiana (Universitas 'Aisyiyah Surakarta, 2023)
Menstruation is a natural thing that happens to a woman and is very important and needs special attention because menstruation is something that marks the beginning of a woman's biological maturity. The initial age when women start menstruation can vary for each individual depending on internal and external factors that influence. This community service activity was carried out at SDN 1 Papahan, Tasikmadu, Karanganyar by providing Reproductive Health Education related to menstruation to elementary school students with an age range of 10 to 13 years, at which age most of the respondents had entered the menarche period. Problem: there are still many adolescents who do not know about reproductive health. Purpose: to find out and provide knowledge related to reproductive health, especially menstruation. Result: the high enthusiasm of the respondents, as evidenced by the large number of students who asked questions about reproductive health, shows that there are many things that need to be learned related to reproductive health in adolescents that are less or even not discussed in the family or society in general. Conclusion: students experience a lack of knowledge, as evidenced by questions based on myths that develop in society, respondents seem embarrassed to express opinions, because menstruation is considered a taboo subject. After health education, students say they have good and correct new knowledge, and are free from myths that were previously believed and considered disturbing in everyday life based on valid and logical science.